Mekanisme dan Implikasi Hukum Perdamaian dalam Kepailitan Berdasarkan Undang-Undang Nomor 37 Tahun 2004 - Diandra Syifa Rahman; Elisatris Gultom; Sudaryat Permana (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Peace agreements serve as an alternative solution for resolving debts between debtors and creditors, aiming to enable debtors to restructure their debts and maintain business continuity. The peace agreement process is governed by strict procedures, including the submission of a peace plan by the debtor, approval by concurrent creditors through voting, and ratification by the Commercial Court through a homologation hearing. A ratified peace agreement is binding on all concurrent creditors but can be annulled if the debtor fails to fulfill their obligations, as illustrated in the case of PT Perindustrian Njonja Meneer. This study employs a normative legal method with a statutory approach and qualitative data analysis. The findings indicate that the success of a peace agreement depends on the debtor’s compliance and the creditors’ approval.